Pseudo-Scientific Method in Economics - Mayer, Joseph (Econometrica, 1933)
NOT long ago it was stated with some emphasis that a seeming impasse in value theory has been reached, that the systems and points of view of five leading contemporary Anglo-American economists, considered representative and outstanding in England and the United States, are rather bewildering in their contradictions and lack of concordance, and that way out is in sight.' The way out, if there is one, is assuredly the path pursued by other sciences in shaking off the incubus of pseudo-scientific method in the course of their development: by the geometers of ancient Greece who, following the analyses of Aristotle and Plato, freed themselves from Pythagorean mysticism in establishing the system of Euclid; by William Gilbert, who much later proved by painstaking experiment that neither goat's blood nor garlic had anything to do with the phenomena of magnetism; by Francis Bacon, who pled with his contemporaries to cease spinning laborious webs of learning out of no great quantity of matter, and test their ideas against the actual facts of experience; by Robert Boyle, who urged students of chemistry to write plainly and unostentatiously about their experiments and thereby keep men from being stunned, as it were, or imposed upon by dark and empty words. If an impasse has been reached in value theory, it may not seem wholly unwarranted to venture the suggestion that this phase of economic study may be in about the same position today that mathematics was in the days of Pythagoras, that physics was in the days of Gilbert, or that chemistry was in the days of Bacon and Boyle. These sciences have passed their periods of impasse and are making steady headway because they have learned to distinguish the scientific from the pseudo-scientific, to regard hypotheses as tentative and of existential worth unless or until verified, and to eschew dogma of whatever variety. Such reflections, it should be added, if pertinent at all, are meant to apply mainly to value theory with its subjective implications, and not